Self-sensing permanent magnet servo motors - Bottomley, Jack S. (2014)
The use of Permanent Magnet Synchronous Machines (PMSMs) has become widespread across numerous applications and industries. Their high power density, efficiency and accuracy of control make them excellent choices, leading them to become the industrial standard. Two issues concerning PMSMs use in recent years have been associated with the elevated cost of rare earth materials required for the Permanent Magnet (PM) rotor poles and the reliance on a direct rotor position sensor such as an encoder.